IMPLEMENTASI KEBIJAKAN AKUNTASI PEMERINTAH DALAM MANAJEMEN ASET TETAP SATUAN KERJA - Lugas Brillian; Agus Sunarya Sulaeman (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Every fixed asset owned and/or controlled by the central government work unit is part of the state assets which will be presented in Financial Report of Central Government. Accounting for fixed assets to produce LKPP is carried out on a cash basis as regulated in Technical Bulletin 15 concerning Accrual-Based Fixed Asset Accounting. The formulation of the problem discussed is the implementation of accounting policies starting from the classification, recognition, measurement, depreciation, as well as the presentation and disclosure of fixed assets in government work units. The aim is to see the accuracy of the implementation of fixed asset accounting policies in government work units. The government work unit that is the object of research is the regional office of one of the ministries in Lampung Province. Research data retrieval is done by interview and document method.